2015
DOI: 10.1007/s12161-015-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pressurized Hot Water Extraction of Flavonoids from Momordica foetida Using UHPLC-qTOF-MS and Multivariate Chemometric Approaches

Abstract: Pressurized hot water extraction (PHWE) has been classified as a green extraction technology, which is used for the extraction of bioactive compounds from plants. However, very few optimization strategies for the efficient extraction of bioactive compounds have been done. In the current study, optimization of PHWE of flavonoids from Momordica foetida was attempted with the aid of ultra-performance liquid chromatography-quadrupole time of flight mass spectrometry (UHPLC-qTOF-MS) and multivariate chemometric mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The research on plants of medicinal importance is rapidly increasing at National and International level. [1][2][3] Use of plants as a source of medicine has been inherited and is an important component of the health care system in India. In the Indian systems of medicine, most practitioners formulate and dispense their own recipes; hence this requires proper documentation and research.…”
Section: Introductionmentioning
confidence: 99%
“…The research on plants of medicinal importance is rapidly increasing at National and International level. [1][2][3] Use of plants as a source of medicine has been inherited and is an important component of the health care system in India. In the Indian systems of medicine, most practitioners formulate and dispense their own recipes; hence this requires proper documentation and research.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction yield patterns of each identified metabolite across the extraction temperature profile were graphically described by the box-and-whiskers plots using IBM SPSS software version 22 (SPSS/IBM, Chicago, Illinois) (Khoza et al, 2015). A one-way analysis of variance (ANOVA) was performed to test for differences in the recovery patterns of identified metabolites across the different extraction temperatures using the above mentioned statistical software.…”
Section: Discussionmentioning
confidence: 99%
“…A one-way analysis of variance (ANOVA) was performed to test for differences in the recovery patterns of identified metabolites across the different extraction temperatures using the above mentioned statistical software. Mean values of extraction yields were compared by Tukey's post hoc test and means were deemed to significantly differ if p ≤ 0.05 as indicated on the box-and-whisker plots (Khoza et al, 2015). In order to perform multivariate data analysis, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher recovery of total antioxidants was achieved from grape pomace by increasing the extraction temperature [101]. Despite the increase in efficiency by increase in temperature, excess temperatures can result in degradation of thermolabile analytes, hence the need for optimization [100,102]. The Subcritical Water Extraction and Its Prospects for Aflatoxins Extraction in Biological Materials http://dx.doi.org/10.5772/intechopen.68706 recovery of carvacrol and thymol from Zataria multiflora between 100 and 175°C indicated that recoveries increased steadily with the increase in temperature up to 150°C, then a degradation phenomenon followed with a noticeable burning smell [103].…”
Section: Temperaturementioning
confidence: 99%